2012
DOI: 10.1002/macp.201200119
|View full text |Cite
|
Sign up to set email alerts
|

Residue Stabilization in the Fire Retardancy of Wood–Plastic Composites: Combination of Ammonium Polyphosphate, Expandable Graphite, and Red Phosphorus

Abstract: Combinations of different common flame retardants in wood–plastic composites (WPCs) are tested to identify synergistic or antagonistic effects with the goal of improving the fire performance of WPCs. Flame retardants investigated are expandable graphite (EG), ammonium polyphosphate (APP), and red phosphorus (RP) and combinations of two of them are used. The fire behavior is studied by cone calorimetric measurements. Additional thermogravimetry is used for further investigations. The fire tests show that EG has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 24 publications
0
48
1
2
Order By: Relevance
“…Expandable graphite may act as a intumescent flame retardant for some polymers [18][19][20][21][22][23] with polyethylene [24] and polyurethane foams being the primary substrates for EG [15,21].…”
Section: Graphite Intercalation Compounds (Gics) Possess Guest Molecumentioning
confidence: 99%
“…Expandable graphite may act as a intumescent flame retardant for some polymers [18][19][20][21][22][23] with polyethylene [24] and polyurethane foams being the primary substrates for EG [15,21].…”
Section: Graphite Intercalation Compounds (Gics) Possess Guest Molecumentioning
confidence: 99%
“…However, the worm‐like intumescent char generated by EG upon burning or heating is usually fragile and fluffy and easily destroyed by heat convection and flame pressure during combustion process . Plenty of works have shown that the combination of EG and red phosphorus (RP) or APP can increase fire retardancy of many polymers substantially and the synergistic effect derives from increased quality of intumescent char in condensed phase . As to the reason for the increased fire retardancy, Braun et al figured that EG could crack the formed residue layer due to its expansion and the combinations of EG with RP or with high amounts of APP were able to suppress this cracking, which conduced to fire retardancy of the polymer .…”
Section: Introductionmentioning
confidence: 99%
“…However, WPCs show an increased fire risk in comparison with wood because of the high heating value of polyolefin polymers [4]. To reduce the flammability of WPCs, many methods were used to treat the WPCs, and the most expeditious method used to acquire flame retardancy was the incorporation of fire retardants during the compounding process [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%